The experience of hepatitis C treatment for people with a history of mental health problems: An interpretative phenomenological analysis. (July 2015) - Ware, K; Davies, J; Rowse, G; Whittaker, S
This qualitative study explores the experience of hepatitis C virus treatment for people with pre-existing mental health problems within a large city hospital. Four men and four women with pre-existing mental health problems who had received hepatitis C virus treatment took part in semi-structured interviews which were analysed using interpretative phenomenological analysis. A central theme of 'Self, stigma and change' was identified which interlinked with three other main themes of 'Coping and responding to treatment', 'Connectedness to others' and 'The impact of information'. These themes and their sub-themes are discussed in relation to existing literature and clinical practice guidelines.